P-803 DNA-FISH analysis in testicular tissue cells of prepuberal patients with Klinefelter Syndrome. (30th June 2022) - Martin Inaraja, M; Alonso, S; Rodriguez, C; Santos, S; Iglesias, M; Prieto, B; Matorras, R; Garcia-Quevedo, L; Vidal, F; Eguizabal, C
Abstract: Study question: Can we accurately assess sex-chromosomes number in testicular cells (germ and somatic) of Klinefelter Syndrome (KS) prepuberal patients by DNA-FISH in paraffin embedded sections? Summary answer: We have evaluated the sex-chromosomes content of testicular cells in KS prepuberal patients and the presence of XY lines evidenced a gonadal mosaicism status. What is known already: Prepuberal boys with Klinefelter Syndrome usually have fertility problems in adulthood, mainly azoospermia. Due to the symptoms cause by the disease, Spermatogonial Stem Cells (SSCs) are less abundant and spermatogenesis does not occur. These patients do not have any alternative to restore the fertility in the future. When a boy has both XY and XXY cell lines, this patient is mosaic (46, XY/47, XXY). Meaning some cells could undergo spermatogenesis and generate gametes with normal sex-chromosomes number. The aim of this work is to test if KS patients diagnosed as pure can have testicular cell lines with XY chromosome number (mosaic). Study design, size, duration: We obtained samples from human prepuberal patients diagnosed with pure Klinefelter Syndrome (47, XXY) for the last 5 years. Testicular biopsy fragments are fixed for histological studies and other fragments are cryopreserved. Some fragments are used for immunofluorescence and subsequently processed by DNA-FISH to determine the sex-chromosomes content of testicular cells. Participants/materials, setting, methods: In this study, we used 10 prepuberal patients with KS and 5 prepuberal patients with other fertility problems with normal chromosome set as controls. We performed immunofluorescence to determine expression of germ cells (VASA) and SSCs (MAGEA4) markers and somatic cells markers such as Leydig cells (StAR) and Sertoli cells (SOX9). Afterwards, we perform DNA-FISH, with probes specific for chromosomes X and Y and chromosome 18 as a control. Main results and the role of chance: The methodology used allows cytogenetic characterization of testicular tissue in paraffin embedded sections. Testicular mosaicism has been observed in all patients diagnosed as pure KS. We have observed a degree of mosaicism of 66-80% in SSCs, of 20-50% in Sertoli cells and of 30-50% in Leydig cells. We pursued a protocol with a good FISH efficiency that allows colocalization of previous immunocharacterized testicular cells. Limitations, reasons for caution: The DNA-FISH technique is made just in a single paraffin section of each KS patient testicular sample. Due to the limited and difficulty to obtain KS testicular tissue, we use a limited number of samples. Wider implications of the findings: We succeed to demonstrate the mosaicism of testicular cells in prepuberal patients that are diagnosed with KS. Thus, the better understanding of the SSCs with normal chromosome set (XY) could be useful for future in vitro expansion and stem cell therapies. Trial registration number: not applicable